The Role of Teachers in the Context of Multicultural Education to Promote Islamic Values - Umar, Sofyan (Journal La Edusci, 2024)
This study explores the role of teachers in promoting Islamic values within multicultural education settings, examining perspectives on integration, challenges faced, and strategies employed. It aims to understand how educators navigate cultural dynamics while fostering ethical development and cultural awareness among students. A qualitative research approach was employed, utilizing semi-structured interviews with educators and educational experts. Participants were selected based on their experience in integrating Islamic values into curriculum and educational practices. Data were analyzed thematically to uncover patterns and insights regarding teachers' perceptions and practices. The result of the research showed that teachers perceive their role as pivotal in integrating Islamic values, viewing it as essential for nurturing ethical behavior and cultural understanding among students. Challenges identified include resistance from stakeholders and resource limitations. Strategies employed include adapting curriculum materials, fostering open dialogue, and enhancing cultural sensitivity. Successful examples highlight the positive impact of integrating Islamic values on students' ethical development and cultural awareness within educational settings.